Providing Opportunities for Flow Experiences and Creative Problem-Solving through Inquiry-based Instruction - Kristy Kowalske Doss (Global Education Review, 2018)
In order to compete globally in the 21st Century, students must have the skills to design their own projects and understand how to navigate the wealth of information available at their fingertips. One of the most important tools is to be able to investigate ideas and implement a plan of action in order to answer questions that have not been explored. These creative problem-solving skills are essential when students design problems and projects during student-driven inquiry. Using action research, instructors evaluated student perceptions and responses to a student-driven inquiry project in an eighth grade honors language arts class. Using interviews and observations, instructors investigated students’ attitudes and experiences throughout the thirteen-week unit of study, focusing on student perceptions of the instructional environment. Students described engagement with topic and process due to choice and authenticity. They described experiencing flow, the state where students become completely engaged in their work, when challenge, motivation, desire, and drive come together to produce optimal outcomes. Themes emerged in how choice influenced the experience of flow during the creative process and how the classroom environment nurtured overcoming obstacles through creative problem solving.